Answer: Choice A
===============================================
Step-by-step explanation:
If we replace x with 0, then we get...
f(x) = 3x^2-8x+2
f(0) = 3(0)^2 - 8(0) + 2
f(0) = 3(0) - 8(0) + 2
f(0) = 0 - 0 + 2
f(0) = 2
Showing that the input x = 0 leads to the output y = f(x) = 2
The answer is between choice A and choice D because of this. Something like choice B is eliminated because this table shows x = 0 leading to y = -3 which is not correct.
-----------
Let's plug in x = 1
f(x) = 3x^2-8x+2
f(1) = 3(1)^2 - 8(1) + 2
f(1) = 3(1) - 8(1) + 2
f(1) = 3 - 8 + 2
f(1) = -5 + 2
f(1) = -3
So x = 1 leads to y = -3. We can rule out choice D and confirm it is choice A.
We don't need to try other x values since we have the answer, but I recommend practicing with other x values to help confirm that the first table is the answer.